Influence of Transformational Leadership and Teacher Collaboration on Teachers’ Ability in Implementing Interdisciplinary Learning - Gaspersz, Eibel John (Academy of Education Journal, 2024)
In today’s world, it is not enough for students to just learn from a single-track learning. Moreover, it is even more important for students as well as teachers to tackle issue they learn in the classroom from various points of views, one way is through an interdisciplinary learning approach. In order for teachers to be competent in applying interdisciplinary learning, the right type of leadership needs to guide these teachers. Besides the right type of leadership, teachers cannot tackle a particular issue on their own, there needs to be a collaboration among the teachers. The purpose of this quantitative study is to analyse the influence of transformational leadership and teacher collaboration on teachers’ ability in implementing interdisciplinary learning at XYZ Schools. Forty-seven teachers at XYZ Schools completed the online questionnaires. The path analysis through PLS SEM method was employed to test the proposed hypothesis. The results showed that transformational leadership has a positive influence on teachers’ ability in implementing interdisciplinary learning. Added to that, teacher collaboration has a positive influence on teachers’ ability in implementing interdisciplinary learning. Also, transformational leadership has a positive influence on teacher collaboration.